(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The paper presents a stochastic gamma process model to account for both population (i.e sampling) and temporal variability associated with a degradation process that typically increases the probability of failure with the aging of a structure. The proposed method is more versatile than the random-variable degradation rate model commonly used in the structural reliability literature. The reason being that the random rate model cannot capture temporal variability associated with evolution of degradation. The paper also describes two methods for estimating parameters of the gamma process to facilitate its practical engineering applications. Little is known of the effects of long term GH replacement on bone mineral content (BMC) and bone mineral density (BMD) in elderly GH -deficient (GHD) adults using Stochastic Degradation model. This study shows that GH replacement increases lumbar (L2 - L4) spine and femur neck BMD and BMC not only in younger but also in elderly GHD patients. So Mathematical result supports the notion that long term GH replacement is also useful in elderly GHD patients.